LEARNER LEXICOGRAPHERS IN ESL CLASSROOMS - Jesa, M.; M, P rabeesh. (International Journal of Psychosocial Rehabilitation, 2020)
Teaching vocabulary has an important role in English teaching to ensure efficiency. The present paper presents the prospects of the corpus-based approach for vocabulary enhancement. The objective of the study is to develop a corpus-based material for vocabulary teaching. The authors have designed lessons with this approach targeting enrichment of vocabulary among secondary school students. The paper also presents a few strategies developed by the investigators for a corpus-based session. The authors analysed the first three units of standard 8 text book prescribed by Kerala SCERT and identified learning outcomes related to the language element of vocabulary items. Context Resource Materials from real life were pooled independently and with the help of British National Corpus(BNC). The different phases of corpus-based approach classroom are also discussed in the study. Corpus based approach equips the learner to be an autonomous interpreter and researcher in the English language classroom.